Impacts of Reallocation of Resource Constraints on the Northeast Economy of Brazil - Geoffrey Hewings; Chokri Dridi; Joaquim Guilhoto (European Regional Science Association (ERSA), 2005)
The present paper explores the role of water and energy resource constraints and allocation on the Northeast Brazil economy. The analysis centered on the creation of an intergrated model in which an econometric-input-output model was linked with a linear programming optimization model for resource allocation. Over the period 1999-2012, the impact on the six agricultural sectors was to reduce their output and employment by 15% annually. The reduction in employment in the rest of the economy was a little over 1% annually. However, since the agricultural sectors continue to employ a significant percentage of the labor force, the aggregate loss of employment amounted to 6% of the total regional employment on average, translating into 1 million jobs annually. When water allocation and energy resource allocations are considered simultaneously, the re-allocations are more limited, resulting in a loss of 0.78 million jobs annually. These results suggest the need for an active link between policy making and economic development when resource constraints are present. Some balance has to be provided between allocation and reallocation on the one hand perhaps driven by concerns with economic efficiency against anticipated losses of employment for part of the labor force with few other alternatives.
Keywords: 330